Walking with the Asafo of Ghana : an ethnographic account of Kormantse Bentsir warrior music - Aduonum, Ama Oforiwaa (Eastman/Rochester studies in ethnomusicology, 2022)
"What is Asafo ndwom (music)? How and when is it performed? What is the state of this tradition that once served as the bedrock of the societies? How does Asafo enact the past and serve as archives for the people? In an attempt to answer these questions, Walking with the Asafo of Ghana investigates the musical pasts of a warrior association. The book is an ethnography of walking, organized into eight chapters. Each chapter ends with an "ethnographic voice," in which Aduonum sums up the main ideas. It is Aduonum's attempt at an anticolonial and decolonialist African musicology, one that subverts and decenters white racial framing of research, analysis, and presentation, disrupting how Euro-American concepts frame our ways of telling and experiencing ndwom. Aduonum's goal on this trajectory is to tell her story, create something new, and chart a new path. Through this fluid and complex book, she repositions African Elders' knowledge as "epistemologies of decolonization and de-coloniality" and centers the stories shared by local Fante scholars. The text is polyvocal, multimodal, multiperspective, performative, reflexive, and dialogic, informed by the structure of Asafo ndwom, appellations, proverbs, her mentors' tellings, and "embodied" calling and responding. It is a performative scholarly discourse, ndwom-based: a performance. As a celebration of Asafo, those warriors who insisted their lives matter, the text is meant to be read and performed"--